The complete mitochondrial genome of Encyrtus infelix (Hymenoptera: Encyrtidae) - Mei Xiong; Qing-Song Zhou; Yan-Zhou Zhang (Mitochondrial DNA. Part B. Resources, 2019)
The mitochondrial genome of the Encyrtus infelix was sequenced and it is the first completed mitochondrial genome of species in the family Encyrtidae (Hymenoptera: Chalcidoidea). This mitochondrial genome is 15,698 bp in length with 37 classical eukaryotic mitochondrial genes and an A + T-rich region. All the 13 PCGs begin with typical ATN codons. Among them, seven genes terminate with TAA, one with TA– and five with T––. All of the 22 tRNA genes range from 56 to 70 bp with typical cloverleaf structure except for trnS1, whose dihydrouridine (DHU) arm forms a simple loop. Gene directions and arrangements are similar to Eurytoma sp. mitochondrial genome. Encyrtus infelix also has a dramatic gene rearrangement, the placements of some genes are peculiar to Chalcidoidea. Phylogenetic analysis highly supported the monophyly of both Chalcidoidea and Pteromalidae.